Mental Health Treatment Patterns for Anxiety and Depression among Women in Nepal - Sharma, Tilak Prasad (Asian Journal of Population Sciences, 2025)
The main objective of this article is to assess different patterns of treatment for anxiety and depression for women in Nepal. There is increasing global consciousness about mental health issues; however, there remain considerable research and practice deficiencies as far as Nepali women are concerned. The justification of the study is to determine the main challenges women face in accessing mental health care in Nepal and to assess the quality of care provided to women. The study used data from the most recent survey, the 2022 NDHS, and a stratified sampling technique to assess the response of a nationally representative sample of 7,442 women categorized based on socio-economic status and region. The factors that have been determined are age, education, wealth, ethnicity, and regional divisions. The treatment-seeking behavior and the service utilization were determined through descriptive statistics. The study reveals that women who were elderly, educated, and wealthy enjoyed better treatment for depression than marginalized and those in rural areas. Lack of structures and financial constraints prevented professional care and drug usage. The majority of the participants depended on care from their close relatives. The study confirms that culturally appropriate approaches should be used for depressed Nepalese people. The changes should involve investment in infrastructure in rural areas, integrating mental health into primary care, and achieving cost reduction by subsidization. Thus, The intervention must be evaluated in future studies to determine if improvements in equity and mental health outcomes are to be made successfully.